الخطاب القرآني في صيانة العقل من الإلحاد : دراسة تحليلية - قطان، لانا خياطة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
his research addresses the powerful Quranic intellectual proof and the matter of Atheism with its decline. It aims to demonstrate the holy Quran's intellectual proofs, as it is the best reliable and successful way to address atheism issue. Through descriptive and analytical methods, the researcher presents a thoroughly introduction by elicitation the Islamic integral methodology with all its intellectual proofs (characteristics and intellectual scientific attributes) and the Quranic Methodologies Properties. Furthermore, the research included the Atheism types, history and reasons as the researcher studied in depth the atheist character attributes, and the basis of irrational atheism. Then the research looked in depth in the strength of the Qur'anic discourse impact on Muslim and non-Muslim intellect, and its actual effect on both Islamic and western worlds. Especially whom are with different religious backgrounds (Christian, atheist and Muslim). The researcher started with “Maurice Bucaille” experience representing the Christian (Catholic) beliefs. Then “Jeffrey Lang” experience representing the Atheism beliefs. Ending with “Muhammad Shahrour” experience representing Islamic beliefs. The researcher also showed their methods via studying the holy Quran and accordingly the research distinguished the proper methods from the poor. In addition, how far it is correct and agreeable with the Quranic Methodology with the fact that it is intellectual, logical and innate nature. As well as dialectical, convincing and objective, based on historical accounts and with its educational, scientific, inimitability objective methodology. One of this research interests was to study the methodologies, which the scholars used in studying the holy Quran as well as how objectively neutrality they were. Beside the importance of knowing the scholars' backgrounds beliefs it is as important as much to know if their approach was righteous in presenting a credible knowledge in their writings. The contradiction was clear with the previous conducted studies examples. As for “Maurice Bucaille” (who stayed as Christian) based on his historical and comparative critical approach it had reinforced the legitimacy of Islam, holiness of the Quranic revelations and the prophet hood evidence of Muhammad. On the other hand, “Jeffrey Lang” who sought truth rationally, logically learning genuinely in his intellectual journey, he had become a Muslim and believed in the holy Quran inspite of language and environmental barriers, by adopting the scientific intellectual approach and objective interpretation. As for the Muslim “Muhammad Shahrour”, he did not provide in his research anything except unrest contradicting approach, by adopting the linguistic deconstructive Interpretation, which opened the door to various individual interpretations and judgments and the abolition of Sharia law as its alienation approach to Islam far as much from any knowledge, reason and logic.